Case series: Using laryngeal mask airway to enhance the radiological evaluation and staging of cancers involving the larynx: A novel technique - Abdullah Aljaafari; Haytham Raad; Aysegul Munar; Ali H. Hasan; Omar Sabra (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract The diagnosis and staging of head and neck tumors requires proper clinical, endoscopic, and radiological evaluation. Currently, imaging techniques such as Magnetic Resonance Imagining (MRI) and Computed Tomography (CT) are used for head and neck tumors but are limited in showing involvement of different hypopharyngeal sub‐compartments. Several maneuvers have been developed to improve visualization of the head and neck area; however, they demonstrated minimal benefit. In this case series, patients with tumors involving the hypopharynx are studied. A laryngeal mask airway was used to stent the hypopharynx to assess the extent of the disease by creating real space between mucosal surfaces. This case series aims to describe the impact of using laryngeal mask airway on the evaluation of cancers involving the hypopharynx.